Investigating the Impact of Domestic Sewage on Asphalt Concrete Pavement Strength - Ahmed, Afzal; Ali, Sajjad; Ahmed, Ashar; Khan, Farah (Engineering, Technology & Applied Science Research, 2024)
This study evaluates the impact of exposing asphalt pavement to sewage and fresh water. In total, 87 samples were prepared, where half of them were immersed in sewage and the others were immersed in freshwater. The Marshall mix design method was adopted for the preparation of samples. Three immersed samples were tested for stability and flow every 24 hours in both fresh water and sewage, comparing the results with a control sample. The samples immersed in fresh water lost their stability and flow after 11 days, while the ones immersed in sewage water lost their stability and flow after 9 days. Furthermore, the loss in stability for samples immersed in fresh water and sewage after 14 days was found to be 38.8 and 55.6%, respectively. The results revealed that sewage water affects asphalt concrete pavement more severely than freshwater. Finally, it was concluded that proper drainage and adequate supplemental sewerage systems are necessary to maintain the desired strength of the pavement throughout its design life.